High Secured Low Power Multiplexer-LUT Based AES S-Box Implementation - Pammu, Ali Akbar (2016)
We propose a Multiplexer Look-Up-Table (MLUT) based Substitution-Box (S-Box) implementation for the Advanced Encryption Standard (AES) algorithm. There are two key features in the proposed MLUT based S-Box. First, it is implemented based on 256-byte to 1-byte multiplexer with a 256-byte memory instead of the conventional implementation of employing multiplication inversion in GF(28) and affine transformation. Thus, our proposed S-Box is simpler in circuit implementation and lower in power dissipation. Second, our S-Box is 30× more secured against the Side Channel Attack (SCA) based on Correlation Power Analysis (CPA), as our proposed S-Box exhibits smaller variance in its power dissipation profile for different processed data. Based on the measurement results of AES-128 implemented on the Sakura-X FPGA board, our proposed S-Box dissipates only 1.9mW and features 5.5× lower power than the conventional S-Box implementation. Our proposed MLUT S-Box design is also highly secured as the CPA attack on the AES with our proposed S-Box implementation requires 13540 power traces. This is significantly higher than the conventional S-Box which requires only 445 power traces to uncover the same secrete key.